One for the money, two for the show? The number of designated market makers and liquidity - Erik Theissen; Christian Westheide (University of Cologne, Centre for Financial Research (CFR), 2022)
Prior research has established that the presence of designated market makers (DMMs) in an electronic open limit order book increases liquidity. We analyze whether the presence of additional DMMs results in a further improvement in liquidity. Using data from Deutsche Börse's Xetra system we find that increases in the number of DMMs significantly improve liquidity, and vice versa for decreases in the number of DMMs. Our results are confirmed when we use an instrumental variables approach to overcome potential endogeneity issues.
Keywords: G10; G14; 330; Designated market makers; Liquidity